Pengembangan Scrapbook 3d Kearifan Lokal Sejarah Monpera Sumatra Selatan Pada Pembelajaran IPS Kelas V Sekolah Dasar - Ulfa, Maria; Lian, Bukman; Aryaningrum, Kiki (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The aim of this research is to develop a 3D Scrapbook of local wisdom on the history of Monpera, South Sumatra on life events, subtheme 1, national events during the colonial period that is valid, practical and effective in class V at SDN 140 Palembang. Researchers use the R&D (Research and Development) development method with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. The media was validated by 2 expert validator lecturers validating the material and language and 1 teacher validating the material. This subject was tested, namely 14 class V students at SD Negeri 140 Palembang. The research resulted in the development of 3D Scrapbook media for the local wisdom of the history of Monpera, South Sumatra which is valid, practical and effective. With the results obtained, the validity percentage was 88%, the practicality percentage was 89% as seen from the students’ responses, and the effectiveness percentage was 94.2%.